The Missing Link : Fostering Positive Citizen-State Relations in Post-Conflict Environments - von Kaltenborn-Stachau, Henriette (World Bank, Washington, DC, 2017)
The aim of this study is to convince national and multilateral policy makers of the importance of the public sphere concept for democratic governance and strategic post-conflict assistance planning with the objective of positive and sustainable change in current post-conflict assistance policy and practice. The study introduces the conceptual thinking underlying the public sphere framework and, citing evidence from different countries, highlights its relevance and calls for its application in post-conflict environments. For practitioners the study provides a public sphere assessment toolkit and a toolbox for interventions. It also offers concrete examples and recommendations on how to address the specific governance challenges identified through a public sphere analysis in three countries: Timor-Leste, Liberia and Burundi.